Family Support And Lonely Elderly In Padang Bulan Kelurahan, Medan New District, Medan City - Juni Magdalena (Institute Of Computer Science (IOCS), 2022)
Family support is provided by a family to increase family adaptation and health, especially in elderly people because they have undergone physical, mental, and psychological changes. One of the psychological problems which is often undergone by elderly people is loneliness which becomes a stressing experience in elderly people which can influence their prosperity. The objective of the research was to identify the correlation between family support and elderly people’s loneliness at Padang Bulan village, Medan Baru Subdistrict, Medan, using descriptive method. The samples were 66 old people, taken by using purposive sampling technique. The data were gathered from May to June, 2015. Reliability test was done by using cronbach alpha method with the samples of 30 old people with the result of 0.906 for questionnaires on family support and 0.754 for questionnaires on loneliness. The data were analyzed by using univatriate analysis, using computerization with descriptive analytic test. The result of the research showed that 37 respondents (56.1%) had sufficient family support, and 47 respondents (71.2%) did not feel lonely. It is recommended that families give support maximally, keep communication with elderly people so that they can adapt in their old age, and lessen their loneliness in order to increase the life quality. The next researches were expected to study the influence of family support and old people’s loneliness on their life quality.